Biodiagnostics in an era of global pandemics—From biosensing materials to data management. Issue 2 (18th June 2021) - Broza, Yoav Y.; Haick, Hossam
Abstract: The novel corona virus SARS‐CoV‐2 (COVID‐19) has exposed the world to challenges never before seen in fast diagnostics, monitoring, and prevention of the outbreak. As a result, different approaches for fast diagnostic and screening are made and yet to find the ideal way. The current mini‐review provides and examines evidence‐based innovative and rapid chemical sensing and related biodiagnostic solutions to deal with infectious disease and related pandemic emergencies, which could offer the best possible care for the general population and improve the approachability of the pandemic information, insights, and surrounding contexts. The review discusses how integration of sensing devices with big data analysis, artificial Intelligence or machine learning, and clinical decision support system, could improve the accuracy of the recorded patterns of the disease conditions within an ocean of information. At the end, the mini‐review provides a prospective on the requirements to improve our coping of the pandemic‐related biodiagnostics as well as future opportunities. Abstract : This review aims to present a broad overview on the biodiagnostic challenges and potential technological solutions in the era of global pandemics. From the development of new sensors and principals, thorough the establishment of diagnostic approaches and monitoring applications, and ending with management and data analysis challenges.